The innovative use of health information in public health policy across EU-Member States. (13th November 2019) - Haneef, R; Oyen, H Van; Gaidelyte, R; Zeynep, O; Pérez-Gomez, B; Haaheim, H; Palmieri, L; Mathis-Edenhofer, S; Majek, O; Gallay, A
Abstract: Background: Health information systems both at the national and international level play a key role in ensuring that timely and reliable evidence is used for operational and strategic decision making inside and outside the health sector. The availability of data generated from different sources is increasing with the possibility to link these data sources together. However, more efficient data generation processes are required to use data collected for different purposes initially, as well as advanced statistical techniques to generate comparable and timely health information. The main objective is to explore the innovative use of health information for better public health policy across the Member States. Methods: As part of InfAct, we have conducted as survey among EU-MS to describe the innovative use of data sources. We are collecting inspiring examples on the innovative use of health information based on national or European data networks involved with health policy-making at national, regional or local level. We are further developing generic methods to estimate health indicators using machine learning techniques and mathematical modelling. Results: These approaches will generate a roadmap on the innovative use of health information across Member States, enlarge the existing list of health indicators estimated from linked data and/or advanced statistical techniques, inform on the implications of these indicators in health policy with inspiring examples from Member States, and provide methodological guidelines for using linked data and advanced statistics to estimate health indicators, and composite outcome measures. Conclusions: This work will highlight the gaps in the innovative use of data sources, and improve the comparability of health indicators and the capacity of EU-Member states to apply innovation for increased relevance and timeliness of health information for public health policy-making.